Literatur Review : Studi Penggunaan Antibiotik Terhadap Pasien Ulkus Diabetikum - Yuliana, Dewi; Hasmi, Nur; Lolo, Andi Maulana (PHARMACY UMI JOURNAL SYSTEM, 2024)
Diabetic ulcers are open wounds on the surface of the skin due to macroangiopathy complications resulting in vascular insufficiency and neuropathy, and can develop into infections due to the entry of germs or bacteria and the presence of high blood sugar which is a strategic place for the growth of germs so that an amputation can occur if blood sugar is too low. the higher it is. The purpose of this study is to find out how the development of treatment using antibiotics for diabetic ulcer disease. The research method is that this study uses literature reviews, in searching literature sourced from 2 databases (Pubmed and Google Scholar) using keywords according to the theme. In contrast to previous studies, this study focuses on the development of treatment using antibiotics in the latest diabetic ulcer patients. The amount of literature used is 13 journal articles. Where the results showed that conservative treatment such as long-term oral and parenteral antibiotics proved effective in patients with diabetic foot ulcers, negative pressure wound therapy methods, Moist Wound Healing, silver type antimicrobials (ActicoatTM), dressings have proven effective in patients.